Starvation Survival Response of Mycobacterium tuberculosis - Parish, Tanya (American Society for Microbiology, 2003)
The ability of Mycobacterium tuberculosis auxotrophs to survive long-term starvation was measured. Tryptophan and histidine auxotrophs did not survive single-amino-acid starvation, whereas a proline auxotroph did. All three auxotrophs survived complete starvation. THP-1 cells were also able to restrict the growth of the tryptophan and histidine auxotrophs.